Efficacy of Rice Husk Nanosilica as A Caries Treatment (Dentin Hydroxyapatite and Antimicrobial Analysis) - Aprillia, Iffi; Alinda, Sylva Dinie; Suprastiwi, Endang (European Journal of Dentistry, 2022)
Objective Rice husk nanosilica has a porous, amorphous structure with a silica (SiO2) surface. Silica interacts with calcium ions to form hydroxyapatite and can induce the formation of reactive oxygen species (ROS), which harm microorganisms. This research determines the effect of rice husk nanosilica on the increase in dentin hydroxyapatite and its antimicrobial effects against Streptococcus mutans.Materials and Methods We divided 27 dental cavity samples into three groups (n = 9). Group 1: normal dentin, Group 2: demineralized dentin, Group 3: demineralized dentin treated with rice husk nanosilica. The samples were analyzed using X-ray diffraction (XRD) to evaluate the formation of dentin hydroxyapatite. To analyze the viability of S. mutans after exposure to 2% nanosilica rice husk, we conducted an antimicrobial MTT assay.Statistical Analysis The Kruskal–Wallis test evaluates the formation of dentin hydroxyapatite, and the t-test evaluates the viability of S. mutans.Results There was an increase in the amount of dentin hydroxyapatite after the application of rice husk nanosilica compared with the control group (normal dentin), and 2% rice husk nanosilica had an antimicrobial effect (p < 0.005) in the group exposed to it.Conclusion Rice husk nanosilica can induce the formation of dentin hydroxyapatite and has antimicrobial effects.
Keywords: nanosilica; rice husk; hydroxyapatite; Streptococcus mutans; antimicrobial